2010
DOI: 10.1182/blood.v116.21.4247.4247
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intracellular Concentration of Reactive Oxygen Species Mediated the Deficient Hematopoiesis of Iron Overload Bone Marrow

Abstract: 4247 Iron overload is caused by multiple blood transfusion and excess gastrointestinal absorption, leading to most of the mortality and morbidity associated with anemia diseases (i.e. aplastic anemia, myelodysplastic syndromes, thalassemia and myelofibrosis). It can cause tissue damage and ultimately dysfunction of visceral organs (mainly in the heart, liver, and endocrine glands). Nevertheless, it is unknown whether iron overload affects the hematopoiesis of bone marrow (BM). In recent years, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…A recent study revealed that the suppressed erythroid differentiation induced by iron overload was mediated by ROS and could be restored by iron chelator or antioxidant (14). Our preliminary study also proved that iron overload affected the function of hematopoietic stem/progenitor cells by the production of ROS (15). Although these findings may partly explain how iron overload affects the hematopoiesis, there is still no answer to the question whether hematopoietic environment is affected during the process and whether ROS-related signaling pathway participates in this process.…”
supporting
confidence: 74%
“…A recent study revealed that the suppressed erythroid differentiation induced by iron overload was mediated by ROS and could be restored by iron chelator or antioxidant (14). Our preliminary study also proved that iron overload affected the function of hematopoietic stem/progenitor cells by the production of ROS (15). Although these findings may partly explain how iron overload affects the hematopoiesis, there is still no answer to the question whether hematopoietic environment is affected during the process and whether ROS-related signaling pathway participates in this process.…”
supporting
confidence: 74%
“…In fact, iron overload in the bone marrow has been shown to increase ROS concentrations in erythroid cells, granulocytes, and CD34+ cells, and this was associated with decreased hematopoietic colony formation relative to that in normal bone marrow. These findings confirmed that ROS signaling played a role in deficient hematopoiesis in iron-overloaded bone marrow [ 8 ]. Another in vitro study showed that free iron inhibited colony formation by erythroid and granulocyte-macrophage progenitors and reduced the size of colonies in a dose-dependent manner [ 9 ].…”
supporting
confidence: 75%
“…It is known that iron is the main catalyst of ROS in an organism, and a growing body of evidence demonstrates that there is a positive correlation between ROS levels and LIP [ 12 , 13 ]. This finding prompted examination of whether IO induced oxidative stress in BM-MSCs in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary research revealed that under iron overload conditions, MSCs were deficient in proliferation and exhibited increased apoptosis. This progressed relative to catalyzing oxidative stress, and there was a positive correlation between ROS levels and labile iron pool (LIP) [ 12 , 13 ]. It has been known that the effect of IO on hematopoietic stem/progenitor cells involved cellular senescence and apoptosis by up-regulating ROS level [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%